2010
DOI: 10.1155/2010/878356
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Features of Hepatitis B Virus Genotypes among Immigrants in Southern Italy

Abstract: Background/aims. This study aims to determine the distribution and clinical features of HBV-genotypes in a population of immigrants affected by HBV-infection. Methods. Between 01/2003 and 03/2009, 1623 immigrants were tested for HBV-infection. Biochemical and virological activities were determined in HBsAg-positive patients; HBV-genotypes were determined, by the INNO-LiPA HBV Genotyping, in the subjects with HBV DNA detectable. In every patient we evaluated the stage and classified the infection as inactive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…On the other hand, positivity to markers of active HBV infection (acute or chronic carrier) among immigrants was equivalent to that reported in Spain [11], but it was about tenfold higher than that described in the Italian population (10.4% vs. 1.5%) [12], and also in other studies conducted in Southern Italy [13,14]. In our country, HBsAg positivity had a consistent downward trend over the past 30 years as a result of the improvement in the social-economical conditions, the decreased intrafamilial spread, a better knowledge of both transmission routes and prevention measures.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, positivity to markers of active HBV infection (acute or chronic carrier) among immigrants was equivalent to that reported in Spain [11], but it was about tenfold higher than that described in the Italian population (10.4% vs. 1.5%) [12], and also in other studies conducted in Southern Italy [13,14]. In our country, HBsAg positivity had a consistent downward trend over the past 30 years as a result of the improvement in the social-economical conditions, the decreased intrafamilial spread, a better knowledge of both transmission routes and prevention measures.…”
Section: Discussionsupporting
confidence: 52%
“…In conclusion, migration flows from highly endemic countries, that are constantly increasing in our region, could play a role to determine a partial but progressive modification of the local HBV/HCV/HIV epidemiology, as well as the introduction of viral genotypes that are actually not common for our geographical area but potentially correlated with a greater liver disease severity/progression and a worse pharmacologic treatment response [14,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study [35] that determine HBV genotype among immigrants to Italy (East Europe, sub-Saharan Africa, East -Asia, Central Africa, and Middle East], indicated that genotype E forms 45.13%, while 18.1% genotype D, 15.3% genotype B, 13.2% genotype C, 4.9% genotype A and 3.5% mixed genotypes (A-D). They found that genotype A was associated to Somali, B and C to Chinese, D to Pakistani, E to Eritrean, A-D mixed genotypes to Pakistani.…”
Section: Disccussionmentioning
confidence: 99%
“…But immigrants modify the normal geographical distribution of hepatitis B virus genotype, with the introduction of non D genotype [35]. Thus population movement within the same country and migration between countries must be taken into consideration and follow up studies for genotyping at time interval is essential global issue.…”
Section: Disccussionmentioning
confidence: 99%
“…The cccDNA (co-valently closed circular DNA), which acts as the major transcriptional template for the virus, is central to the durability of HBV infection and persists as an episome in infected hepatocytes. It can persist after antiviral therapy and even after the apparent clearance of the infection [5]. …”
Section: Hbv (Hepatitis B Virus)mentioning
confidence: 99%